The possible hierarchical scales of observed clumps in high-redshift disc galaxies. Issue 1 (21st June 2019) - Behrendt, M; Schartmann, M; Burkert, A
ABSTRACT: Giant clumps on ∼kpc scales and with masses of $10^8\rm {-}10^9 \, \mathrm{M_{\odot }}$ are ubiquitous in observed high-redshift disc galaxies. Recent simulations and observations with high spatial resolution indicate the existence of substructure within these clumps. We perform high-resolution simulations of a massive galaxy to study the substructure formation within the framework of gravitational disc instability. We focus on an isolated and pure gas disc with an isothermal equation of state with T = 10 4 K that allows capturing the effects of self-gravity and hydrodynamics robustly. The main mass of the galaxy resides in rotationally supported clumps which grow by merging to a maximum clump mass of $10^8 \, \mathrm{M_{\odot }}$ with diameter ∼120 pc for the dense gas. They group to clump clusters (CCs) within relatively short times ($\ll 50 \, Myr$ ), which are present over the whole simulation time. We identify several mass and size scales on which the clusters appear as single objects at the corresponding observational resolution between ${\sim } 10^8 \, \rm{and}\, 10^9 \, \mathrm{M_{\odot }}$ . Most of the clusters emerge as dense groups and for larger beams they are more likely to be open structures represented by a single object. In the high-resolution runs higher densities can be reached, and the initial structures can collapse further and fragment to many clumps smaller than the initial Toomre length. In our low-resolution runs, the clumps directly form on larger scales 0.3–1 kpc with $10^8\rm {-}10^9 \, \mathrm{M_{\odot }}$ . Here, the artificial pressure floor which is typically used to prevent spurious fragmentation strongly influences the initial formation of clumps and their properties at very low densities.